2004
DOI: 10.1111/j.1460-9568.2004.03586.x
|View full text |Cite
|
Sign up to set email alerts
|

Attention and executive function deficits in chronic low‐dose MPTP‐treated non‐human primates

Abstract: Parkinson's disease (PD) is a complex disorder consisting of motor deficits coupled with dysfunction in cognitive domains that are dependent upon the integrity of the frontal lobes and/or the fronto-striatal axis. Although it is increasingly acknowledged that PD patients have attentional and executive function deficits, it has been difficult to model these in nonhuman primates because of the nature of the cognitive tasks that have been used previously. The present studies were conducted to further define the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 37 publications
4
63
0
Order By: Relevance
“…Impaired ability to sustain spatial attention or to focus attention, deficit in motor readiness and planning, and impaired time estimation were observed in these animals. 70 Collectively, these cognitive alterations are consistent with attention and executive functional deficits following MPTP intoxication, which is very similar to some of the cognitive alterations seen in PD patients. As emphasized by Stern,68 it is also remarkable to note that none of the symptomatic individuals who were intoxicated with MPTP showed neurological signs others than those expected for PD; a similar statement may be true for MPTP-injected monkeys.…”
Section: The Human Parkinsonian Neurotoxin 1-methyl-4-phenyl-1236supporting
confidence: 64%
See 1 more Smart Citation
“…Impaired ability to sustain spatial attention or to focus attention, deficit in motor readiness and planning, and impaired time estimation were observed in these animals. 70 Collectively, these cognitive alterations are consistent with attention and executive functional deficits following MPTP intoxication, which is very similar to some of the cognitive alterations seen in PD patients. As emphasized by Stern,68 it is also remarkable to note that none of the symptomatic individuals who were intoxicated with MPTP showed neurological signs others than those expected for PD; a similar statement may be true for MPTP-injected monkeys.…”
Section: The Human Parkinsonian Neurotoxin 1-methyl-4-phenyl-1236supporting
confidence: 64%
“…Cognitive impairments evidenced by poor performances on constructive, verbal fluency and executive function tests were demonstrated in MPTP patients. 68,69 Apparently, not in humans 68,69 but in monkeys intoxicated with MPTP, 70 deficits in maintenance of a response set and difficulties in shifting attentional sets were also found. Impaired ability to sustain spatial attention or to focus attention, deficit in motor readiness and planning, and impaired time estimation were observed in these animals.…”
Section: The Human Parkinsonian Neurotoxin 1-methyl-4-phenyl-1236mentioning
confidence: 98%
“…In this case, before the screen is lowered the examiner alerts the animal to the baiting of the well to ensure that the monkey pays attention to the wells. Interestingly, this protocol did not change control animals' score, but significantly improved the performance of MPTPtreated monkeys (Decamp et al 2004a). An additional variant of VDR is the modified delayed response (MDR) task, in which the attentional demands of the task are manipulated to allow good performance in trials with low attentional load and impaired performance in trials with higher attentional load by increasing the length of time of cue presentation.…”
Section: Mptp-based Nonhuman Primate Modelmentioning
confidence: 91%
“…However, a recent ¹¹C-raclopride study of spatial working memory concluded that executive dysfunction in patients with early PD is associated with impaired nigrostriatal function and that mesocortical dopaminergic function is well preserved in early PD. 22 Similarly, data from several studies in monkeys with minimum motor defi cits after low and slow MPTP exposure have shown defi cits in executive function and attention, 101 which were best explained by a nigrostriatal lesion. 102 These fi ndings suggest that dysfunction of cortico-basal ganglia associative areas secondary to dopamine depletion might have an important role in early executive problems in patients with PD.…”
Section: Pathophysiology Of Executive Dysfunctionmentioning
confidence: 99%